Purposes and Quality of Graduate Education in the Management Sciences - Cook, S. L. (Management Science, 1970)
The questions asked in Professor Churchman's letter of November 17, 1969, sound simple enough, but it would take a book to answer them fully. They are questions fundamental to the future of the management sciences. The statement below attempts to summarize the purpose and aims of the OR/Systems Section of the Department of Industrial Administration in the University of Aston in Birmingham, and to relate these to present and planned graduate courses. Since the present courses commenced less than two years ago and planned courses are some way off, most of our aims have yet to be achieved.